Pengaruh Ukuran Ovarium Dan Diameter Oosit Terhadap Kualitas Morfologi Oosit Sapi Bali-Timor Yang Dikoleksi Secara In Vitro - Hermilinda Parera (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
One of the reproductive technology in cattle which growing rapidly is in vitro fertilization techniques for in vitro embryo production. Environmental factors that influence the in vitro embryo development is the diameter of oocytes and ovarian size. Currently, the amount of research on Bali-Timor cattle is still lacking, especially in reproduction tecnology. Kune and Solihat (2007) states that the Bali-Timor cattle have a high fertility rate up to 60-70%. Application of in vitro reproduction technology can improve the genetic quality of livestock by using gametes cells collected from animals. The purpose of this study was to determine the effect of the size of the ovaries and oocytes diameter to the quality of the oocyte morphology of Bali-Timor cattle that were collected by in vitro technique. Oocytes samples of Bali-Timor cattle derived from ovarian which obtained from the slaughter house. Furthermore, the ovaries were grouped based on the size of the ovary, i.e group I (≤1,5 cm); group II (1.6 to 2 cm) and group III (≥2,1cm). Oocytes produced from the ovarian then grouped based on the diameter of the oocytes, i.e group I (110-150μm); group II (151-200μm); group III (201-250μm); group IV (251-300μm); Group V (301-350μm) and group VI (≥ 351μm). The results showed that the quality of the oocyte morphology did not differend significantly (P> 0.05) on ovarian size. Oocyte quality category A (29.78%) and category B (42.55%) were obtained from group III ovarian higher than group II (25% category A, category B 36%) and group I (category A 19.23 %, category B 26.92%), while the diameter of the oocytes had no effect on the percentage of morphological quality of oocytes produced in vitro.